2021
DOI: 10.1126/sciadv.abj1316
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary adaptation of visual pigments in geckos for their photic environment

Abstract: Vertebrates generally have a single type of rod for scotopic vision and multiple types of cones for photopic vision. Noteworthily, nocturnal geckos transmuted ancestral photoreceptor cells into rods containing not rhodopsin but cone pigments, and, subsequently, diurnal geckos retransmuted these rods into cones containing cone pigments. High sensitivity of scotopic vision is underlain by the rod's low background noise, which originated from a much lower spontaneous activation rate of rhodopsin than of cone pigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…In addition to the counterion displacement process, several evolutionary processes of animal rhodopsins, such as the process of color tuning and adaptation of thermal isomerization rates, have been progressively studied. 32,[72][73][74][75] We expect that further studies on the evolution of animal rhodopsins would reveal their divergence and adaptation and their roles in physiology.…”
Section: The Evolution Of Animal Rhodopsinsmentioning
confidence: 99%
“…In addition to the counterion displacement process, several evolutionary processes of animal rhodopsins, such as the process of color tuning and adaptation of thermal isomerization rates, have been progressively studied. 32,[72][73][74][75] We expect that further studies on the evolution of animal rhodopsins would reveal their divergence and adaptation and their roles in physiology.…”
Section: The Evolution Of Animal Rhodopsinsmentioning
confidence: 99%
“…We previously developed a biochemical technique to evaluate the thermal activation rates of recombinant visual pigments purified from cultured cells as an alternative to the electrophysiological techniques using intact photoreceptor cells ( 14 , 25 , 26 , 34 ). This method enables us to quantitatively compare the thermal activation rates of visual pigments under the same experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In these vertebrate species, the multiple types of rods having different color sensitivities are thought to be used for distinguishing colors under scotopic conditions ( 22 , 23 , 24 ). Our recent biochemical analysis revealed that in these noncanonical cone pigments ( i.e., frog blue, nocturnal gecko green, and UV) the thermal activation rates were suppressed to mimic rhodopsin, and this suppression underlies the low noise level in the atypical rods and leads to the acquisition of scotopic color vision in frogs and nocturnal geckos ( 25 , 26 ). Noteworthily, we identified key amino acid residues responsible for the low thermal activation rates of noncanonical cone pigments ( i.e.…”
mentioning
confidence: 99%
“…To investigate the cDNAs of two channelrhodopsin-like genes from V. brassicaformis (CEL94649 and CEM28120) that encode photoactive proteins, we expressed them as recombinant proteins in mammalian HEK293 cells, which have been used for the functional expression of animal rhodopsins and eukaryotic microbial rhodopsins 27 30 . As shown below, since the recombinant CEM28120 protein shows a blue-sensitive anion channeling activity like GtACR2, we refer to the channelrhodopsin-like protein (CEM28120) as V. brassicaformis anion channelrhodopsin-2 (VbACR2).…”
Section: Resultsmentioning
confidence: 99%
“…HEK293T cells were cultured in Dulbecco’s Modified Eagle Medium Nutrient Mixture F-12 (DMEM/F12, Gibco, Thermo Fisher Scientific, USA), supplemented with 10% fetal bovine serum, 0.0625% (w/v) penicillin and 0.01% (w/v) streptomycin under a humidified atmosphere containing 5% CO 2 at 37 °C. The expression plasmids were transiently transfected using the calcium phosphate method 27 , 28 . After 1 day incubation, all- trans -retinal (final conc.…”
Section: Methodsmentioning
confidence: 99%